Allelic and bio-chemical characterization of Indian wheat (Triticum aestivum) varieties and breeding lines for quality traits - PHOUGAT, DIVYA; PREETI, PREETI; SINGH, VIKRAM; YASHVEER, SHIKHA; PANWAR, I S (The Indian Journal of Agricultural Sciences, 2021)
Thirteen released and two elite genotypes of wheat (Triticum aestivum L.) from North-West Plain Zone of India were subjected to biochemical and molecular characterization to study the genetic variability, their grouping and identification using a combination of biochemical and molecular markers during 2014-16 at Department of Genetics and Plant Breeding, COA, CCSHAU, Hisar. HD 2967, WH 1142 and WH 1080 were overall better performing for protein content, sedimentation value, hectolitre weight and grain appearance. A total of 99 and 117 polymorphic bands were detected using ISSR and SSR primers, respectively. The similarity indices for SSR ranged from 0.64 to 0.77 while ISSR showed the range of 0.63-0.92. Present study could be effectively utilized in DNA fingerprinting, identification of wheat varieties and elite lines for bio-chemical traits and determination of seed purity.